Enhancing Partial Packet Recovery in RLNC Using Homomorphic Message Authentication Codes - Fathi, Amin; Pahlevani, Peyman (IEEE communications letters, 2025)
Network coding enhances wireless communication by transmitting coded packets. However, transmission errors often lead to unnecessary packet discards, even when most data remains intact. Existing recovery methods address this issue but suffer from high recovery delays in noisy environments and false positives caused by checksum collisions, resulting in redundant retransmissions. This letter presents a novel method, termed Combined Recovery, which replaces traditional Cyclic Redundancy Check (CRC) codes with Homomorphic Message Authentication Codes (HMAC). By exploiting the homomorphic property of HMACs, Combined Recovery introduces a technique that enables efficient error correction with notably reduced search complexity. Simulation results across various scenarios demonstrate that Combined Recovery eliminates retransmissions and significantly reduces recovery delay, providing a robust and efficient solution for reliable communication over noisy channels.